Annual Review of Gerontology and Geriatrics, 16 (1996) : Focus on Managed Care and Quality Assurance, Integrated Acute and Chronic Care. - Newcomer, Robert (Springer Pub. Co., 1996)
The contributors to this volume provide an overview of each component of the acute and long-term care service continuum, including managed health care, subacute care, nursing homes, community care case management, and private case management. This volume is one of the first efforts to place these varied approaches side-by-side, highlighting the gaps and areas of duplication in the services delivery system. In addition, chapters address the emerging practices in long-term care financing and assisted living as well as the conceptual issues that need to be resolved to achieve acute and chronic ca.